(untitled) (International conference on multidisciplinary science, 2025)
This article examines the current challenges faced by commercial banks in accounting for mortgage loans and outlines actionable strategies for improvement. By leveraging advanced technologies, refining internal processes, and fostering a culture of continuous learning, banks can achieve greater operational efficiency and strengthen their mortgage loan portfolios. The recommendations provided aim to align accounting practices with global standards while enabling banks to meet the demands of an increasingly complex financial landscape.